Model Penilaian Moderasi Beragama Dalam Pembelajaran PAI Untuk Penguatan Karakter Toleran Dan Inklusif - Taufik Taufik; Andi Fitriani Djollong; Usnul Lestari; Hamran Hamran; Syamsuriah Syamsuriah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Religious moderation is a crucial effort in building a tolerant and inclusive character in educational settings, particularly in Islamic Religious Education (PAI) learning. This literature review aims to examine relevant and applicable assessment models for religious moderation in the context of Islamic Religious Education (PAI) learning in schools. A literature-based approach was used to identify concepts, principles, and implementation of assessment models that support the strengthening of students' character. The analysis shows that religious moderation assessments assess not only cognitive aspects but also affective and psychomotor aspects, oriented toward the values ​​of justice, balance, tolerance, and respect for diversity. Effective assessment models include authentic assessments, observation-based attitude assessments, reflective journals, portfolios of moderation values, and collaborative projects across religions and cultures. The implementation of these models strengthens students' spiritual and social dimensions while fostering a peaceful and harmonious school culture. Therefore, developing an assessment model for religious moderation in PAI is a strategic part of creating a generation with moderate, open characters and appreciating differences as part of the nation's diversity.